2015
DOI: 10.1002/ajmg.a.37004
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mosaicism of a novel IKBKG mutation in a male patient with incontinentia pigmenti

Abstract: Incontinentia pigmenti (IP) is an X-linked, dominant genodermatosis usually fatal in utero in males. In rare circumstances, survival is possible due to abnormal karyotype or somatic mosaicism. In this report, the mechanism and significance of loss of detectable mutation in peripheral blood leukocytes of a somatic mosaic male is discussed and an alternative approach to achieving molecular diagnosis presented. A male patient is reported, who initially presented at 2 days of age with a rash and seizure. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Since the identification of IKBKG , about 47 male patients, including ours, were genotyped using DNA extracted from blood samples. IKBKG mutations were found in 21 patients: Δ4–10 rearrangement in 20 cases, including one with Klinefelter syndrome, and one patient with a nonsense IKBKG c.937C>T mutation . The lack of detectable mutation in 26 of 47 of patients could be attributed to the fact that IKBKG mutation was searched for in the leucocytes of peripheral blood samples only.…”
Section: Clinical and Molecular Characteristics Of Seven Male Patientmentioning
confidence: 99%
“…Since the identification of IKBKG , about 47 male patients, including ours, were genotyped using DNA extracted from blood samples. IKBKG mutations were found in 21 patients: Δ4–10 rearrangement in 20 cases, including one with Klinefelter syndrome, and one patient with a nonsense IKBKG c.937C>T mutation . The lack of detectable mutation in 26 of 47 of patients could be attributed to the fact that IKBKG mutation was searched for in the leucocytes of peripheral blood samples only.…”
Section: Clinical and Molecular Characteristics Of Seven Male Patientmentioning
confidence: 99%
“…Fewer than 20% of boys with IP who had genetic testing in the largest series showed an IKBKG mutation in peripheral blood after 3 months of age (2). The current hypothesis is that leukocytes with the mutation undergo selective apoptosis near 3 months of age (3).…”
Section: Discussionmentioning
confidence: 93%
“…Hypercalcemia is most commonly attributed to genetic syndromes or is drug induced in children (1). Incontinentia pigmenti (IP) is lethal in the majority of males, with only 40 rare surviving cases published worldwide as of September 2015 (2)(3)(4)(5). Peripheral eosinophilia and cutaneous vesicles with eosinophils are characteristically present in IP, but we found no prior cases noting hypercalcemia in the 2013 review of male cases and subsequent case reports (6).…”
mentioning
confidence: 98%
“…2,10 Previously, among 28 cases of sporadic male IP patients who underwent molecular genetic analysis, eight patients demonstrated mosaicism with a common exon 4-10 deletion, one patient had 47 XXY, and 19 patients had no IKBKG/NEMO gene mutations/deletion, 11 which indicates that leukocytes with exon 4-10 deletion mutation may undergo selective apoptosis over time. Furthermore, Hull et al 12 reported that in samples obtained from a 5-6-year-old, 46 XY patient with IP, the mutation was identified at a low level in hair roots and urine but not in blood, which had been positive soon after birth. If the gene mutation/deletion is not detected in patients with clinically typical skin lesions, it could be tested in other accessible tissues, namely hair roots or urine.…”
Section: Discussionmentioning
confidence: 99%